Creative Adaptation of Singo Santoso Sakti Dance Group in the Development of Reog Ponorogo Art in Kreteg Hamlet, Lerep Village, Semarang Regency - Wahyu Setyaningsih Sugiyo, Septi; Hartono, Hartono; Wadiyo, Wadiyo (Catharsis, 2019)
Singo Santoso Sakti dance group is a group that has advantages or advantages compared to other groups. The advantage of this group is that it has an attractive performance quality at each attraction. The purpose of this study is to analyze the adaptation and creativity of the Singo Santoso Sakti dance group in the development of the Reog Ponorogo art. The method that is used in this study is qualitative with a choreological approach, and cultural anthropology. Data collection techniques are done by observation, interviews and documents. Data validity uses source triangulation. Data analysis was performed by describing, understanding, interpreting, and evaluating. The research results of the Singo Santoso Sakti dance group in the development of Reog Ponorogo are of two kinds namely adaptation and creativity. The most important finding of the adaptation process is art learning carried out by art practitioners and supported by the community so that Reog Ponorogo is used to meet the needs of life. The findings of creativity involve 4P: pribadi, pendorong, proses dan produk (personal, encouragement, process and product) in the form of performances such as dance movements, floor patterns, dance accompaniment, make-up, fashion, equipment, and venue. Suggestions for Reog Ponorogo dance artists are to always preserve traditional arts in Indonesia and provide opportunities for young people to learn Reog Ponorogo dance in Semarang Regency.